Integrasi Filsafat Pendidikan Islam dalam Praktik Pembelajaran di Pesantren Al-Irsyad Tengaran Kabupaten Semarang - Mujiburrohman, Mujiburrohman; Khamdani, Agus Walid (TSAQOFAH, 2025)
This article examines the integration of Islamic educational philosophy into the teaching practices at Al Irsyad Tengaran Islamic Boarding School, focusing on the application of its ontological, epistemological, and axiological dimensions as the foundation for a holistic educational system. A descriptive qualitative approach was employed, using in-depth interviews with key educators. The findings reveal that Al Irsyad Tengaran implements an educational approach that is not only conceptual but also fully integrated into the curriculum and instructional strategies. The epistemological aspect is reflected in dialogical and reflective approaches to teaching ʿaqīdah-akhlāq, as explained by Ustadz Ahmad Nur Hayun, S.Pd.I. The axiological dimension is embodied in tahfizh activities aimed at internalizing core values, as noted by Ustadz Abdullah Tholib, S.Pd.I. The ontological aspect is demonstrated through the integration of religious and scientific knowledge, as practiced by Ustadz Zaenal Arifin, Lc. This approach aligns with the pesantren's vision to cultivate students who are knowledgeable, ethical, and capable of contributing to the global community. Structural support in the form of educational levels from SDITQ to MA further strengthens the institution’s commitment to producing competent and principled graduates. The study concludes that Islamic educational philosophy is essential as a foundational framework for building a comprehensive and sustainable pesantren education system.